ZAHIRIDDIN MUHAMMAD BOBUR’S CONTRIBUTION TO THE PROSPERITY AND PROSPERITY OF THE COUNTRY - Kadirov Mirsulton Batirovich; Sadykov Mirjalol (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the creative work and achievements of Babur and the Baburids , as well as the chronology of Babur and his partial marches, as well as the views of Babur and the Baburis on creative ethics, prosperity and well-being. combined with high spiritual qualities shi , personalized attention and career to serve as a lesson to make sure that is reflected in the menu.